Prevalence of four viruses in captive Siberian tigers from Northeastern China. Issue 5 (26th February 2022) - Huang, Shuping; Li, Xiang; Guo, Lijun; You, Dan; Xie, Wei; Xu, Haitao; Liu, Dan; Wang, Yulong; Zeng, Xiangwei; Hou, Zhijun; Liu, Enqi; Ma, Liying; et al.
Abstract: Our study investigated the prevalence of feline herpesvirus‐1 (FHV‐1), feline calicivirus (FCV), feline immunodeficiency virus (FIV), and feline leukemia virus (FeLV) in captive Siberian tigers in Northeastern China. A total of 324 blood samples and 33 nasopharyngeal swab samples of Siberian tigers collected from 2019 to 2021 in three cities were investigated by nested PCR. The results showed that 28.1% (91/324) tigers were infected with at least one virus; the positive rates of FHV‐1, FCV, and FIV were 17.3%, 13.6%, and 0.9%, respectively; and the coinfection prevalence was 13.2%. No FeLV‐positive sample was detected. And we found that the blood is the best for FCV, FIV, and FeLV detection, but nasopharyngeal swabs for FHV‐1. By comparing the gD genes, TK gene, and gI gene of FHV‐1, the homology of the three FHV‐1 positive strains in this study was found to be 91.5%–99.9% shared with tigers and domestic cats. Based on a comparison of the nucleic acid sequences of 13 FCV strains, we found that the homology of strain HB‐1926 with the other strains in this study was only about 77.7%, but shared 99.3% and 98.6% homology with Urnaba strain in American cat and TG1 strain in Chinese tiger, respectively. However, the other 12 FCV strains shared 87.1%–87.5% homology compared with the Chinese domestic cats. Phylogenetic tree analysis showed that the HB‐1926 strain was not in the same clade as other strains. The fragments gag ‐p26, pol ‐RT, and pol ‐RNAse of Siberian tiger FIV shared more than 99% homology than domestic cats FIV subtype A. This study demonstrated that captive Siberian tigers in Northeastern China were exposed to FHV‐1, FCV, and FIV, and it is necessary to develop more effective vaccines and improve daily management measures.